(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the advantages and effectiveness of using an individual treatment program in irreversible orthodontic treatments. The study found that treatment programs developed considering patients’ individual characteristics significantly improve the success rate of orthodontic treatments.